Peningkatan Literasi Keagamaan Masyarakat Melalui Ngaji Bersama dan Diskusi Santai bersama Mahasiswa KPM - Meisya Alfina; Alwan Wildani; Alifa Ayassofia; Fikri Husni Fauzan; Novi Fitriyani; Arkhan Ashimudin Sajid; Claora Sinta Kurnia Putri Aprillia; Muhammad Arif Setyawan; Amallya Nur Adzani; Ana Tri Ristiani; Andi Sofan Saputra; Mutaqin; Adnan Firdaus Setyarta; Sri Hartiyah (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
The Community Service Program (KPM) is an implementation of the university’s tridharma, aiming to enhance religious literacy in society through educational and interactive activities. This study aims to analyze the effectiveness of religious programs in improving Islamic understanding within the community. The research employs a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The fidings indicate that activites such as one day one juz, morning assemblies with Asmaul Husna recitation, Festival Anak Sholeh, anand Ngaji Literasi positively impact religious literacy development. These activities not only enhance Islamic comprehension but also strengthen social relationship within the community. Through a participatory approach, KPM students have successfully created a more angaging and accessible religious learning environment. In conclusion, this program is effective in fostering religious literacy and is expected to be sustainable with active community involvement.